Theoretical and practical fundamentals of scientific and educational projects: a case of Ukraine - Olena Bilovodska; Ievgeniia Golysheva; Olena Gryshchenko; Herbert Strunz (Journal of International Studies)
Development of educational and scientific spheres in general and project activity of universities in particular, acquire foreground importance in the modern world. In the article approaches to rendering a term “project” and its basic characteristics are analyzed. Scientific and educational projects are a special type: although they represent a subsidiary activity, they are vital to the image, rankings, prosperity and at some point to competitiveness. The major funding opportunities for scientific and educational projects are generalized. The authors have analyzed the official figures of the State Statistics Service of Ukraine which show the levels of cost funding of scientific and educational projects and describe its main sources in 2010-2015. A study of impact factors on the funding levels of Ukrainian scientific and educational projects by foreign sources was conducted using the method of correlation analysis. According to the results of the conducted analysis, it was determined that activity of international mobility of Ukrainian scientists doesn’t influence the levels of international funding. It was also established that there is a strong inverse relationship between such factors as a share of expenditures on scientific and scientific-technical activities in GDP, a number of organizations involved in scientific and scientific-technical activities and a number of grants for scientific research received from international funds.